PERAN INSTRUMEN EUCS (END USER COMPUTING SATISFACTION) SEBAGAI ASSESMENT TOOLS SYSTEM INFORMASI DARI PERPEKTIF GENDER PENGGUNA PERPUSTAKAAN - Rika Jufriazia Manita; Sri Wahyuni (UIN Imam Bonjol Padang, 2020)
This article explains that the existence of libraries in the modern era requires keeping up with the times by combining information services with information technology. This aims to make the library continue to survive and be able to compete with other information institutions. The goal is to improve the quality of information services in the library. In terms of improving library services, user satisfaction aspects are important in measuring the usefulness and success of information systems in libraries. The method used in this paper is literature study, with a descriptive analysis approach. In this paper the author focuses on research studies using the EUCS (End User Computing Satisfaction) model through a gender perspective approach which will be tested using the EUCS variable in full. The variables include content, accuracy, format, timeliness, ease of use, and speed of access. The author concludes that gender will have a beneficial and easy effect on interest in using information systems in libraries. This can be seen from the fact that men are more influenced by the perceived benefits of using the information system in the library, while women are more influenced by convenience.